1976
DOI: 10.1002/ijc.2910180316
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of syngeneic tumor growth in rats immunized with allogeneic skin grafts

Abstract: The growth of a transplantable tumor (KMT-17) in syngeneic Wistar King Aptekman/Mk (WKA) rats was inhibited by preimmunization with allogeneic normal cells from Donryu strain rats. The phenomenon is referred to as allogeneic cell immunity. A slight inhibition was observed in rats immunized with normal liver, spleen, kidney, embryonal cells, whole blood and white blood cells from allogeneic Donryu rats. A strong inhibition was observed in animals which had rejected allogeneic skin grafts, particularly from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1978
1978
1994
1994

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Cold blocking experiments showed the reaction to be specific. Hosokawa et al (1976) have reported a somewhat similar phenomenon in the case of a methylcholanthrene-induced fibrosarcoma of rats. Animals of the strain of origin immunized with allogeneic skin grafts of some genotypes showed 100 % survival when challenged with the isogeneic tumor.…”
Section: The Altered Self Hypothesismentioning
confidence: 53%
“…Cold blocking experiments showed the reaction to be specific. Hosokawa et al (1976) have reported a somewhat similar phenomenon in the case of a methylcholanthrene-induced fibrosarcoma of rats. Animals of the strain of origin immunized with allogeneic skin grafts of some genotypes showed 100 % survival when challenged with the isogeneic tumor.…”
Section: The Altered Self Hypothesismentioning
confidence: 53%
“…It can be ascribed to a high density of tumor antigens on the hybrid cell surface (Jami and Ritz, 1975), or to a modification of the tumor antigen structure on the membrane, perhaps in association with the gene products of the major histocompatibility complex of the allogeneic part of the hybrid cell (Chen and Watkins, 1970). The inoculation of alloantigens may contribute to increasing the immune response by a non-specific process, as has been previously reported (Invernizzi and Parmiani, 1975;Hosokawa et al, 1976). Another hypothesis to explain the higher immunizing capacity of hybrid cells as compared to tumor cells is that parental tumor cells could release factors which inhibit the immune response (Pikovski et al, 1975;Nelson and Nelson, 1978), while hybrid cells are devoid of such factors.…”
Section: Discussionmentioning
confidence: 84%
“…Altough evidence has accumulated, from both in vivo and in vitro experiments, that some murine tumours do express foreign H-2 specificities (Meschini et al, 1977;lnvernizzi et al, 1977;Pliskin and Prehn, 1978), there is no direct evidence in solid tumour systems that tumour-specific antigens are foreign alloantigens. In fact, the proposal has been made that the in vivo rejection of a tumour-czll challenge following alloimmunization is due to a non-specific phenomenon (Hosokawa et al, 1976). In only one tumour system, murine thymus leukaemia, has it been definitively demonstrated that the tumour-associated TL antigen is an alloantigen in other strains of mice (Boyse et al, 1964).…”
Section: Discussionmentioning
confidence: 99%